The influence of workload and competence on employee performance through satisfaction as an intervening variable (Study on the Inpatient Installation of RSU Negara) - Putra, I Putu Eka Suadnyana Putra; Kusumawijaya, Ida Ketut; Santika, I Putu (PT ARRUS Intelektual Indonesia, 2025)
This study analyzes the effect of workload and competence on employee performance, using satisfaction as an intervening variable. The population was 186 nurses and midwives working in the inpatient installation room of RSU Negara. A sample of 65 was taken using proportional random sampling. Data analysis techniques included validity test analysis, reliability, classical assumptions, and path analysis. The results showed that workload had a negative and significant effect on employee job satisfaction and performance; competence had a significant positive effect on employee job satisfaction and performance; job satisfaction had a significant positive effect on employee performance; workload had a negative effect on employee performance through job satisfaction as an intervening variable at RSU Negara. These results showed that job satisfaction could not be an intervening variable on the effect of workload on employee performance at RSU Negara. Competence had a positive effect on employee performance through job satisfaction as an intervening variable at RSU Negara. These results showed that job satisfaction could be an intervening variable on the effect of competence on employee performance at RSU Negara. The research suggests that management at RSU Negara can reduce workload, improve competence, and increase employee job satisfaction to improve employee performance.